Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1620/tjem.243.133
|View full text |Cite
|
Sign up to set email alerts
|

Association between Nitrogen Stable Isotope Ratios in Human Hair and Serum Levels of Leptin

Abstract: Stable isotope ratios have been reported to be potential biomarkers of dietary intake and nutritional status. High serum levels of leptin, a hormone which regulates energy metabolism and food intake, are associated with insulin resistance and metabolic syndrome. However, little is known about the association between stable isotope ratios and the metabolic risk in humans. We investigated whether the carbon and nitrogen stable isotope ratios in hair are associated with serum leptin levels. Hair samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…In a comparison of diabetic patients with controls, no change in hair δ 15 N was found while the δ 13 C value declined and a relationship was found with haemoglobin A1 glycation (HbA1c), this relationship being mostly visible in males [15]. However, in another cohort, hair δ 15 N correlated to plasmatic leptin concentration (in particular in individuals with high body mass index) but no relationship was found with δ 13 C values [16]. In adolescents or children, the δ 13 C value in fingerstick blood samples or in erythrocytes has been found to increase at high food intake (increased sugar intake or high calory diet) and this seemed to be unrelated to HbA1c or to C 4 sugar consumption [17,40].…”
Section: Isotopes In Human Metabolic Syndrome Diabetes or Nutritional...mentioning
confidence: 91%
See 3 more Smart Citations
“…In a comparison of diabetic patients with controls, no change in hair δ 15 N was found while the δ 13 C value declined and a relationship was found with haemoglobin A1 glycation (HbA1c), this relationship being mostly visible in males [15]. However, in another cohort, hair δ 15 N correlated to plasmatic leptin concentration (in particular in individuals with high body mass index) but no relationship was found with δ 13 C values [16]. In adolescents or children, the δ 13 C value in fingerstick blood samples or in erythrocytes has been found to increase at high food intake (increased sugar intake or high calory diet) and this seemed to be unrelated to HbA1c or to C 4 sugar consumption [17,40].…”
Section: Isotopes In Human Metabolic Syndrome Diabetes or Nutritional...mentioning
confidence: 91%
“…Aa metabolism 13 C, 15 N Collagen [12] Chronic malnutrition and potential growth retardation (stunted children) Aa metabolism 13 C, 15 N Hair [13] Patients with metabolic syndrome Glycaemia Aa metabolism 13 C, 15 N Hair [14] Diabetic patients Sugar metabolism 13 C, 15 N Hair [15][16][17][18]…”
Section: Syphilismentioning
confidence: 99%
See 2 more Smart Citations
“…Although diet is a significant risk factor for hypertension and metabolic diseases [ 6 , 15 , 16 ], little is known regarding the relationship between stable isotope ratios and metabolic risk in humans. Results of recent studies have suggested the possible association of nitrogen stable isotope ratios with metabolic syndrome and serum leptin levels [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%